The Role of Management Accounting Systems in Strategic Sensemaking - Heidmann, Marcus (Wiesbaden Gabler Verlag, 2008)
In order to survive in a competitive environment, top and middle managers need to make sense of strategic issues. Information from the internal and external environment helps managers to relate the firm's strengths and weaknesses to specific opportunities and threats embedded in these issues. Marcus Heidmann explores the role of management accounting systems (MAS) in strategic sensemaking. Based on cognitive theories, the author defines strategic sensemaking as a learning process with observation, interpretation, and communication as the relevant process steps on the individual level. He illustrates the impact of MAS on these cognitive processes by an exploratory multiple-case study design. He shows that managers do not primarily use MAS to identify strategic topics but to search for additional information that helps them to make sense of these issues. In particular, the interactive use of MAS contributes to strategic sensemaking by providing directions and facilitating interactions that help to resolve equivocality of strategic issues
Theoretical Foundation -- Management Accounting Systems and Strategic Sensemaking -- Research Design -- Results of Case Study Research -- Implications and Outlook
Keywords: Accounting